The Role of Film Genre in Transformative Ideological Documentary Analysis of Politics: An Ideological Documentary Analysis of Nelson Mandela: The Living Legend (1918-2013) (The Strategic Review for Southern Africa, 2020)
This article is a critical analysis of the biographical-political documentary entitled Nelson Mandela: The Living Legend (1918-2013), published by the British Broadcasting Corporation as part of its multi-dimensional global media projects. The two-part series narratively outlines an illustrious, albeit significant historic, political and transformative period spanning about 67 years embodied in Mandela's persona as a symbol of the dialectic of resistance and transformation in South Africa. The article employs qualitative content analysis to highlight the producers' use of specific filmic excerpts that frame Mandela as the symbolic figure and transformative leader who reconfigured South Africa's political stalemate to democracy. This is augmented by an ideological analysis of the socio-economic and political milieu premised within the institutional context represented in the documentary. Despite the functional agenda setting role that the film packaging process espouses, the producers' application of Western constructive ideological framing as the epicentre upon which the legendary qualities of Mandela are pivoted is evident. This eventually yields into the focalisation of Mandela's transformative model to highlight as well as demonstrate the benefits of reconciliatory-inclusive politics in facilitating change as opposed to the antics of violence and confrontational conquest often associated with individualist paradigms and politics of patronage. Thus, beyond purveying the protagonist as a symbol of both political influence and moral integrity, particularly during the transition period, the documentary is a vivid mise-en scene that showcases Mandela's charismatic leadership as the prototype befitting the qualities of iconic international statesmanship.
Keywords: Mandela; Nelson Mandela; South Africa; democracy; British Broadcasting Corporation; documentary; biographical; political; mise-en-scene